2022
DOI: 10.1590/0034-7167-2020-1190
|View full text |Cite
|
Sign up to set email alerts
|

Health beliefs and adherence of the elderly to fall prevention measures: a quasi-experimental study

Abstract: Objective: To evaluate the effect of an educational intervention on health beliefs and adherence of elderly people to fall prevention measures. Methods: This is a quasi-experimental study, carried out at the Senior Citizens' Center. Sixty-eight elderly completed the intervention. The intervention consisted of four meetings focused on beliefs about falls and prevention, and the evaluation occurred at baseline and 30 days after completion. Results: The elderly were predominantly women (83.82%), with one to fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(63 reference statements)
0
3
0
2
Order By: Relevance
“…A redução no tempo para conseguir dormir converge com as orientações de higiene do sono ancorada nos princípios do modelo teórico de crença em saúde, no qual o idoso foi encorajado a perceber benefícios de dormir bem e assim realizá--los. Resultados exitosos das orientações de enfermagem foram observados nos estados do Mato Grosso e São Paulo também para o público idoso (17,25) . Nesse contexto, crer na autoeficácia da ação, ou seja, crer em sua capacidade de modular fatores que melhorem o sono intensifica a prática correta, a partir da reformulação da ideia que é previsível sono ruim em idosos (26) .…”
Section: Discussionunclassified
“…A redução no tempo para conseguir dormir converge com as orientações de higiene do sono ancorada nos princípios do modelo teórico de crença em saúde, no qual o idoso foi encorajado a perceber benefícios de dormir bem e assim realizá--los. Resultados exitosos das orientações de enfermagem foram observados nos estados do Mato Grosso e São Paulo também para o público idoso (17,25) . Nesse contexto, crer na autoeficácia da ação, ou seja, crer em sua capacidade de modular fatores que melhorem o sono intensifica a prática correta, a partir da reformulação da ideia que é previsível sono ruim em idosos (26) .…”
Section: Discussionunclassified
“…The reduction in time to fall asleep converges with sleep hygiene guidelines anchored in the principles of the theoretical model of belief in health, in which older adults were encouraged to perceive the benefits of sleeping well and thus realize them. Successful results of nursing guidelines were observed in the states of Mato Grosso and São Paulo, also for older adults (17,25) . In this context, believing in action self-efficacy, i.e., believing in its ability to modulate factors that improve sleep, intensifies the correct practice, based on the reformulation of the idea that poor sleep is predictable in older adults (26) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that interventions that provide information lead to knowledge increment, adherence promotion and favors preventive measures against COVID-19 ( 11 ) . In this regard, a study conducted in Israel reported that, through an educational intervention (short video), they were able to increase the knowledge score on COVID-19, the safety perception, and personal resilience ( 12 ) .…”
Section: Introductionmentioning
confidence: 99%